Targeting casein kinase 1 for cancer therapy: current strategies and future perspectives - Long, Ngo Hoang; Lee, Sook-Jeong (Frontiers in Oncology, 2023)
Casein Kinase 1 (CK1) is a family of serine/threonine protein kinases that play a crucial role in various cellular processes, including cell proliferation, survival, and metabolism. The dysregulation of CK1 expression has been implicated in the development and progression of several types of cancer, making it an attractive target for anticancer therapy. In this review, we provide an overview of the current strategies employed to target CK1 for cancer therapy and discuss the future perspectives in this field. We highlight the different approaches, including small molecule inhibitors, RNA interference, genome editing, and immunotherapies, which hold immense potential for targeted modulation of CK1 activity in cancer cells. Furthermore, we discuss the challenges associated with targeting CK1 and propose potential strategies to overcome these hurdles. Overall, targeting CK1 holds great promise as a therapeutic strategy for cancer treatment, and further research in this area is warranted.